Makna Term Malaikat Dalam Al-Quran Perspektif Semantik Toshihiko Izutsu - Chasanah, Chulsum Layyinatul; Pratama, Pradika Yoga; Lessy, Zulkipli (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
Angels are supernatural creatures created by Allah with various tasks and characteristics given to them. Even though angels are invisible to human senses, the Qur'an proves that the existence and information of angels definitely exists.This research uses the key term angels in the Koran using semantic concepts. The data obtained was by collecting verses that contain the word angel. The primary source was obtained from Toshihiko's book "The Relationship between God and Man". Meanwhile, secondary sources were obtained from journals, theses and websites. The method used is Toshihiko Izutsu's semantic method. Analysis of the words studied uses several stages, including finding basic meaning, relational meaning, synchronic and diachronic aspects. This research aims to find out the word angel in the Koran using Toshihiko Izutsu's semantic perspective. The word angel is mentioned in the Koran 83 times. The word angel has the basic meaning of messenger. Syntagmatically, the word angel includes four meanings, namely: those who obey God's commands and always exalt, those who confirm humans in goodness, those who bring revelation and information from God including happy news for Maryam, and those who take lives. Paradigmatically, the word angel has a synonymous relationship with the words al-Ruh and Harut Marut. Meanwhile, the relationship of anonymity is established with the words Jinn, Devil, and Satan. In the pre-Qur'anic period, the word angel was conceived by pre-Islamic Arabs as well as by the beliefs of people before the revelation of the Koran as very beautiful and attractive creatures. In the Qur'anic period, angels had various glories and nobility but could not be made God or children of God. In the post-Qur'anic era the meaning of angels is seen even more broadly and is not limited to belief.